The Impact of Tanjung Karang Tourism Village on Local Labor Absorption: A Case Study on Loang Baloq Tourism, Mataram City - Jainal Abidin; St. Maryam; Satarudin, Satarudin (English and Tourism Studies, 2024)
This study aims to analyze the impact of the existence of Tanjung Karang tourism village on local employment in Tanjung Karang, Mataram City. The business units in this study are Grocery Micro Small Medium Enterprises, Souvenir Micro Small Medium Enterprises, Fish Culinary Center Micro Small Medium Enterprises, and Homestays. This research uses a qualitative method with a descriptive approach. Data were obtained through observation, interviews, and documentation. Informants were selected using purposive sampling technique. Data analysis used the Miles and Huberman model, namely reducing data, displaying data, and drawing conclusions. The results found that the impact of the existence of the Tanjung Karang tourism village with the Loang Baloq Park tourist attraction on the absorption of local labor in Tanjung Karang is still relatively low. It can be seen from the number of workers who work as owners of Micro, Small and Medium Enterprises that are more often not selling and have not even been seen selling again for a long time, preferring to work elsewhere and there are also some who are unemployed. Homestay owners also experience obstacles such as a lack of interest from tourists to stay overnight due to the unattractive form of community housing and a community culture that is prone to social unrest due to the presence of tourist lodging in community homes. These conditions make employment in Tanjung Karang tourism village relatively low.